Blood pressure changes after renal denervation at 10 European expert centers - Persu, A; Jin, Y; Azizi, M; Baelen, M; Völz, S; Elvan, A; Severino, F; Rosa, J; Adiyaman, A; Fadl Elmula, F E; Taylor, A; Pechère-Bertschi, A; et al. (Journal of human hypertension, 2014)
We did a subject-level meta-analysis of the changes (Δ) in blood pressure (BP) observed 3 and 6 months after renal denervation (RDN) at 10 European centers. Recruited patients (n=109; 46.8% women; mean age 58.2 years) had essential hypertension confirmed by ambulatory BP. From baseline to 6 months, treatment score declined slightly from 4.7 to 4.4 drugs per day. Systolic/diastolic BP fell by 17.6/7.1 mm Hg for office BP, and by 5.9/3.5, 6.2/3.4, and 4.4/2.5 mm Hg for 24-h, daytime and nighttime BP (P0.03 for all). In 47 patients with 3- and 6-month ambulatory measurements, systolic BP did not change between these two time points (P0.08). Normalization was a systolic BP of <140 mm Hg on office measurement or <130 mm Hg on 24-h monitoring and improvement was a fall of 10 mm Hg, irrespective of measurement technique. For office BP, at 6 months, normalization, improvement or no decrease occurred in 22.9, 59.6 and 22.9% of patients, respectively; for 24-h BP, these proportions were 14.7, 31.2 and 34.9%, respectively. Higher baseline BP predicted greater BP fall at follow-up; higher baseline serum creatinine was associated with lower probability of improvement of 24-h BP (odds ratio for 20-μmol l(-1) increase, 0.60; P=0.05) and higher probability of experiencing no BP decrease (OR, 1.66; P=0.01). In conclusion, BP responses to RDN include regression-to-the-mean and remain to be consolidated in randomized trials based on ambulatory BP monitoring. For now, RDN should remain the last resort in patients in whom all other ways to control BP failed, and it must be cautiously used in patients with renal impairment.
Keywords: výsledek terapie; kombinovaná terapie; Denervation; Male; antihypertenziva; hypertenze; Combined Modality Therapy; Essential Hypertension; denervace; Europe; Kidney; mužské pohlaví; Hypertension; Treatment Outcome; Evropa; lidé; ženské pohlaví; Humans; ledviny; Antihypertensive Agents; ambulantní monitorování krevního tlaku; Blood Pressure Monitoring, Ambulatory; Female; esenciální hypertenze; lidé středního věku; Middle Aged